2018
DOI: 10.1186/s12933-018-0663-6
|View full text |Cite
|
Sign up to set email alerts
|

Glitazones and alpha-glucosidase inhibitors as the second-line oral anti-diabetic agents added to metformin reduce cardiovascular risk in Type 2 diabetes patients: a nationwide cohort observational study

Abstract: ObjectiveMetformin is the standard first-line drug for patients with Type 2 diabetes (T2DM). However, the optimal second-line oral anti-diabetic agent (ADA) remains unclear. We investigated the cardiovascular risk of various ADAs used as add-on medication to metformin in T2DM patients from a nationwide cohort.MethodsT2DM patients using different add-on oral ADAs after an initial metformin therapy of > 90 days were identified from the Taiwan National Health Insurance Database. Five classes of ADAs, including su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 51 publications
1
27
0
1
Order By: Relevance
“…Also, they report an elevated risk for add‐on sulfonylureas compared with add‐on thiazolidinediones (specifically pioglitazone). Similar findings have been found from data from other healthcare systems, such as the Taiwan National Health Insurance Database , the Swedish National Diabetes Registry and the Korean National Health Insurance Database .…”
Section: Discussionsupporting
confidence: 87%
“…Also, they report an elevated risk for add‐on sulfonylureas compared with add‐on thiazolidinediones (specifically pioglitazone). Similar findings have been found from data from other healthcare systems, such as the Taiwan National Health Insurance Database , the Swedish National Diabetes Registry and the Korean National Health Insurance Database .…”
Section: Discussionsupporting
confidence: 87%
“…Twenty years ago, experimental evidence showed that lowering blood glucose reduced the risk of microvascular complications among patients with type 2 diabetes [33,60,61]. Several studies have subsequently indicated that metformin decreased mortality and adverse cardiovascular events [62][63][64][65][66]. A large nationwide study revealed that patients treated with metformin had significantly lower all-cause mortality than those treated with sulfonylureas (including glimepiride, glyburide, glipizide, and tolbutamide) [54].…”
Section: Discussionmentioning
confidence: 99%
“…In Asian T2DM patients without prior cardiovascular diseases, the real-world data also showed controversial protective effects of pioglitazone. Chan et al [32] demonstrated that pioglitazone added to metformin, compared to sulfonylurea plus metformin, may have fewer major cardiovascular events in T2DM patients. But another real-world study did not show the protective effects of pioglitazone on IS prevention [33].…”
Section: Discussionmentioning
confidence: 99%